Cybersicherheit und Rollenwandel - Schünemann, Wolf J.; Harnisch, Sebastian; Artmann, Stefan (Zeitschrift für Politikwissenschaft, 2018)
The US’ loss of reputation due to the Snowden-revelations did not lead to a change in cooperative behaviour in cybersecurity politics. This article explains this by pointing out the continuity in role attribution by allied governments and thereby links role theoretical IR-research with quantitative and qualitative instruments from discourse analysis. The US, as “basic service provider”, “idea-structure provider”, and “protector”, have adopted the role-set of a “custodian” during the decades of the evolution of the internet. This paper shows that these roles never saw veritable contestation by government actors. Hence, no change in the US’ role in international cybersecurity politics and internet governance took place.